2010
DOI: 10.1100/tsw.2010.32
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Add-On in Treatment of Depressed Patients with Insulin Resistance: a Pilot Study

Abstract: A number of cross-sectional studies have suggested an association between insulin resistance (IR) and affective disorders. However, limited data exist on potential changes in IR in a prospective treatment of depression. The present pilot study tested the hypothesis that improvement of IR with the addition of an insulin-sensitizing agent would improve mood in nondiabetic patients with unipolar or bipolar depression, who had surrogate blood markers suggestive of IR. Surrogate IR-criteria blood markers were fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 36 publications
3
84
0
Order By: Relevance
“…Such effects were reported for the thiazolidinediones rosiglitazone and pioglitazone (Saubermann et al, 2002; Ali et al, 2006; Zhao et al, 2006; Asghar et al, 2007; Strum et al, 2007; Eissa Ahmed and Al-Rasheed, 2009; Mittal et al, 2009; Rasgon et al, 2010; Kemp et al, 2011). For instance, rosiglitazone, one of the insulin sensitizers of the thiazolidinedione class, induces an antidepressant-like effect in the tail suspension and forced swim tests in mice, reducing immobilization and floating behavior (Eissa Ahmed and Al-Rasheed, 2009).…”
Section: Introductionmentioning
confidence: 63%
“…Such effects were reported for the thiazolidinediones rosiglitazone and pioglitazone (Saubermann et al, 2002; Ali et al, 2006; Zhao et al, 2006; Asghar et al, 2007; Strum et al, 2007; Eissa Ahmed and Al-Rasheed, 2009; Mittal et al, 2009; Rasgon et al, 2010; Kemp et al, 2011). For instance, rosiglitazone, one of the insulin sensitizers of the thiazolidinedione class, induces an antidepressant-like effect in the tail suspension and forced swim tests in mice, reducing immobilization and floating behavior (Eissa Ahmed and Al-Rasheed, 2009).…”
Section: Introductionmentioning
confidence: 63%
“…A clinical trial in patients with mild Alzheimer disease and type 2 diabetes mellitus found that patients who received pioglitazone showed improved cognition, compared to patients who received placebo (Landreth et al, 2008). Another study has shown that addition of an insulin-sensitizing agent may improve mood in nondiabetic patients with major depressive disorder or bipolar disorder, who had blood biomarkers indicative of insulin resistance (Rasgon et al, 2010a). Further studies are warranted to determine if these findings can be validated.…”
Section: Personalized Medicine Approaches Using Circulating Biomarkersmentioning
confidence: 99%
“…It has been suggested that insulin resistance is a part of the pathophysiology of affective disorders, and that improvement of insulin resistance may reduce the severity of depressive symptoms (Rasgon et al, 2001;Rasgon and Jarvik, 2004). Treatments of type 2 diabetic patients with insulin sensitizers rosiglitazone and pioglitazone improve not only metabolic derangements, but also affective disorders (Kemp et al, 2009;Wagner et al, 2009;Rasgon et al, 2010;Kemp et al, 2012). Rhodila species have been used widely to treat fatigue and depression (Kelly, 2001;Panossian et al, 2010).…”
Section: Neuschwandermentioning
confidence: 99%